A lung-on-a-chip array with an integrated bio-inspired respiration mechanism. Issue 5 (18th December 2014) - Stucki, Andreas O.; Stucki, Janick D.; Hall, Sean R. R.; Felder, Marcel; Mermoud, Yves; Schmid, Ralph A.; Geiser, Thomas; Guenat, Olivier T.
Abstract : The effects of respiration movements on primary lung cells from patients are investigated on an easy to handle lung-on-a-chip. Abstract : We report a lung-on-a-chip array that mimics the pulmonary parenchymal environment, including the thin alveolar barrier and the three-dimensional cyclic strain induced by breathing movements. The micro-diaphragm used to stretch the alveolar barrier is inspired by the in vivo diaphragm, the main muscle responsible for inspiration. The design of this device aims not only at best reproducing the in vivo conditions found in the lung parenchyma but also at making the device robust and its handling easy. An innovative concept, based on the reversible bonding of the device, is presented that enables accurate control of the concentration of cells cultured on the membrane by easily accessing both sides of the membranes. The functionality of the alveolar barrier could be restored by co-culturing epithelial and endothelial cells that form tight monolayers on each side of a thin, porous and stretchable membrane. We showed that cyclic stretch significantly affects the permeability properties of epithelial cell layers. Furthermore, we also demonstrated that the strain influences the metabolic activity and the cytokine secretion of primary human pulmonary alveolar epithelial cells obtained from patients. These results demonstrate the potential of this device and confirm the importance of the mechanical strain induced by breathing in pulmonary research.